Legal Analysis of Shareholders as an Organ of The Company Viewed From Commercial Code - Prasasti Dyah Nugraheni (Law and Justice, 2020)
This paper aims to explain the authority possessed by the members of Shareholders in the Articles of Association. In Articles of Association of Limited Liability Company, it contains regulations governing an operational activity that will become the purpose of Limited Liability Company. The Articles of Association have compelling and binding nature for all members of Shareholders, all members of the Board of Commissioners, and all members of the Board of Directors. Members of Shareholders are an organ owned by Limited Liability Company whose authority owned by all members of the Board of Commissioners and all members of the Board of Directors. One of the authorities possessed by the members of Shareholders is to appoint the members of the Board of Commissioners and members of the Board of Directors. In this paper, the author used research methods of normative and juridical, meaning that the writing method is carried out by analyzing secondary legal materials or library materials to find solutions to problems of legal problems arising and to use a problem approach based on laws or legal rules in general about the powers of the shareholders that apply to such event and approach the problem based on a conceptual basis. The results show that the position of the shareholders is not higher than and even equal to the position of the Board of Commissioners and Board of Directors. Whereas in the Indonesian Commercial Code, it stipulates that the position of shareholders is the highest in a Limited Liability Company.Keywords: Authority of Shareholders; Company Law Number 40 of 2007; Limited Liability Company